1996
DOI: 10.1074/jbc.271.41.25569
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Protein-tyrosine Phosphatase SH-PTP2 by a Tyrosine-based Activation Motif of a Novel Brain Molecule

Abstract: BIT (a brain immunoglobulin-like molecule with tyrosine-based activation motifs) is a brain-specific membrane protein which has two cytoplasmic TAMs (tyrosine-based activation motifs). Using the Far Western blotting technique, we detected association of a 70-kDa protein with the tyrosine-phosphorylated TAMs of BIT. A mouse brain cDNA library in gt11 was screened for this association, and two positive clones encoding tyrosine phosphatase SH-PTP2 were isolated. SH-PTP2 has two SH2 domains and is believed to func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
90
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 46 publications
2
90
0
Order By: Relevance
“…One possible explanation is that the two SH2 domains of SHP-2 have di erent binding speci®city. When comparing the sequences surrounding naturally occuring association sites for SHP-2, Tyr763 is quite similar to the association sites found in a number of other molecules (Table 1) (Case et al, 1994;Fujioka et al, 1996;Jackson et al, 1997;Ohnishi et al, 1996;Ottinger et al, 1998;Sugimoto et al, 1994). Many of these molecules have an alanine residue in position +1, an acidic residue in position +2, followed by either leucine or isoleucine in position +3.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…One possible explanation is that the two SH2 domains of SHP-2 have di erent binding speci®city. When comparing the sequences surrounding naturally occuring association sites for SHP-2, Tyr763 is quite similar to the association sites found in a number of other molecules (Table 1) (Case et al, 1994;Fujioka et al, 1996;Jackson et al, 1997;Ohnishi et al, 1996;Ottinger et al, 1998;Sugimoto et al, 1994). Many of these molecules have an alanine residue in position +1, an acidic residue in position +2, followed by either leucine or isoleucine in position +3.…”
Section: Discussionsupporting
confidence: 69%
“…It has previously been shown that Tyr1009 in the PDGF breceptor binds to SHP-2 (Kazlauskas et al, 1993), and that the association between the SH2 domains of SHP-2 and its target proteins triggers activation of the phosphatase activity of SHP-2 Pluskey et al, 1995). Simultaneous occupancy of both SH2 domains by phosphopeptides is required for full activation of the phosphatase activity of SHP-2 (Eck et al, 1996;Jackson et al, 1997;Ohnishi et al, 1996;Pluskey et al, 1995). This suggests that additional autophosphorylation sites in the PDGF b-receptor might contribute to the activation of SHP-2.…”
Section: Introductionmentioning
confidence: 99%
“…A consensus cytoplasmic sequence found in these inhibitory receptors, referred to as the immunoreceptor tyrosine-based inhibitory motif or ITIM, binds to the SH2 domaincontaining phosphotyrosine phosphatases (PTPs) SHP1 and SHP2. More recent e orts (Fujioka et al, 1996;Ohnishi et al, 1996;Kharitonenkov et al, 1997) led to the isolation and cloning of new inhibitory receptors in neurons and epithelial cells based on their binding to SHP2. Signal-Regulatory Proteins [SIRPs (Kharitonenkov et al, 1997); murine homolog SHPS-1, or SHP substrate 1 (Fujioka et al, 1996)], a family of membrane glycoproteins and putative substrates of the SHP1 and SHP2 phosphatases, are unique members of the inhibitory receptor family whose members are ubiquitously expressed.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently characterized a membrane glycoprotein, SHPS-1 (SHP substrate-1) Noguchi et al, 1996;Yamao et al, 1997) (also known as SIRP1 (Kharitonenkov et al, 1997) or BIT (Ohnishi et al, 1996)), whose extracellular region contains three homologous immunoglobulin-like domains and multiple N-linked glycosylation sites. The cytoplasmic region of SHPS-1 contains four tyrosine residues followed by XX(L/V/I) sequences (Y408ADL, Y432ASI, Y449ADL and Y473ASV), which represent potential tyrosine phosphorylation sites.…”
Section: Introductionmentioning
confidence: 99%
“…SHPS-1 appears to be a docking protein, such as IRS-1, Gab-1 (Holgado-Madruga et al, 1996) and DOS (Herbst et al, 1996), that recruits SHP-2 from the cytosol to a site near the plasma membrane in response to various growth factors or cell adhesion. The synthetic phosphotyrosyl peptide containing sequence surrounding Tyr 449 and Tyr 473 increases the phosphatase activity of SHP-2 in vitro, suggesting that the binding of SHP-2 to tyrosine-phosphorylated SHPS-1 may stimulate the PTPase activity of SHP-2 (Ohnishi et al, 1996). After activation induced by binding to SHPS-1, SHP-2 may dephosphorylate and dissociate from SHPS-1, stimulating the RAS ± MAP kinase cascade through dephosphorylation of an unknown target protein.…”
Section: Introductionmentioning
confidence: 99%